Mechanism of the right ventricular reverse remodeling after balloon pulmonary valvuloplasty in patients with congenital pulmonary stenosis: A three-dimensional echocardiographic study - Amr Mansour; Azza Abdallah Elfiky; Alaa Sakran Mohamed; Dina Adel Ezzeldin (Wolters Kluwer Medknow Publications, 2020)
Background and Objectives: The main effect of pulmonary stenosis is a rise in right ventricular pressure. This pressure overload leads to multiple changes in the shape, dimensions, and volumes of the right ventricle (RV) that are reversed after the relieve of the valve obstruction. We thought to study the changes in the RV in patients undergoing balloon pulmonary valvuloplasty (BPV) using three-dimensional (3D) echocardiography. Subjects and Methods: The study included 50 patients with isolated valvular pulmonary stenosis who underwent BPV at our hospital from December 2016 to August 2017; echocardiography was recorded preprocedural and 3 months after the procedural. Results: The median age of the study group at the time of the procedure was 2.7 years. The indexed RV wall thickness, basal, and mid-right ventricular dimensions decreased significantly after the procedure (P < 0.005), and the longitudinal dimension increased significantly after the procedure (P < 0.005). The end-systolic and the end-diastolic volumes (EDVs) by 3D echocardiography increased insignificantly (P > 0.05), and the right ventricular function increased significantly (P < 0.05), indicating that the changes in the EDVs were more than the changes in the end-systolic volumes. Conclusions: There are several factors that interplay together and result in reverse remodeling of the RV after BPV including regression in the RV hypertrophy; changes in the interventricular septal morphology, bowing, and mobility; and changes in the ventricular geometry and dimensions, rather than changes in the ventricular volumes.